Analysis Of The Age Of Uncollectible Accounts Receivable At The Tirta Umbu Drinking Water Company Of Nias Regency - Lase, Lely Kristiani; Zebua, Dedi Irawan; Zebua, Serniati; Zai, Kurniawan Sarototonafo (Universitas Dehasen Bengkulu, 2025)
This study aims to analyze the Uncollectible Accounts Receivable at Perumda Air Minum Tirta Umbu, Nias Regency, and its impact on the company’s liquidity and financial sustainability. The research method employs a quantitative approach with receivables aging analysis (aging schedule) based on customer arrears reports and financial statements for the period 2022–2023. The results indicate weak effectiveness in managing receivables, influenced by customer payment delays, suboptimal collection systems, and limited internal supervision. The study recommends improvements in collection procedures, the implementation of strict sanctions for delinquent customers, strengthening of administrative systems, and training for collection staff to enhance the effectiveness of receivables management and maintain the financial health of Perumda Air Minum Tirta Umbu, Nias Regency.